Rethinking minority stress: A social safety perspective on the health effects of stigma in sexually-diverse and gender-diverse populations. (July 2022) - Diamond, Lisa M.; Alley, Jenna
Abstract: For over two decades, the minority stress model has guided research on the health of sexually-diverse individuals (those who are not exclusively heterosexual) and gender-diverse individuals (those whose gender identity/expression differs from their birth-assigned sex/gender). According to this model, the cumulative stress caused by stigma and social marginalization fosters stress-related health problems. Yet studies linking minority stress to physical health outcomes have yielded mixed results, suggesting that something is missing from our understanding of stigma and health. Social safety may be the missing piece. Social safety refers to reliable social connection, inclusion, and protection, which are core human needs that are imperiled by stigma. The absence of social safety is just as health-consequential for stigmatized individuals as the presence of minority stress, because the chronic threat-vigilance fostered by insufficient safety has negative long-term effects on cognitive, emotional, and immunological functioning, even when exposure to minority stress is low. We argue that insufficient social safety is a primary cause of stigma-related health disparities and a key target for intervention. Highlights: Sexually- and gender-diverse (SGD) individuals have pronounced health disparities, typically attributed to excess stress. In addition to excess stress, SGD individuals also experience insufficient social safety. Social safety (social connection, inclusion, and protection) are fundamental human needs. Those without sufficient social safety experience chronic threat-vigilance, which has negative long-term health effects. To reduce SGD health disparities, we need to reduce minority stress while also increasing social safety.